THE IMPLEMENTATION OF CONTEXTUALIZATION IN TEACHING VOCABULARY TO ELEMENTARY STUDENTS (REACT: Relating, Experiencing, Applying, Cooperating, and Transferring) - Tuti Rohayati (Journal of English and Education, 2013)
The primary focus of this study is to determine the effect of contextualization on students’ vocabulary mastery and to investigate the students’ responses toward contextualization in teaching and learning vocabulary. In this study, contextualization is employed through REACT (Relating, Experiencing, Applying, Cooperating, and Transferring) strategy proposed by Crawford (2001). The samples of this study arestudents of thefifth grade of one elementary school in Bandung that are chosen purposively. By using a quasi-experimental with nonequivalent groups design, both experimental and control groups (30 students in each group) are given pretest of multiple-choice test to find out their initial ability. Then, the experimental group is treated by using contextualization for four meetings. Meanwhile, the control group is treated by using a traditional (non-REACT) method; the grammar translation method. An interview is administered to find out students’ responses toward contextualization. The findings indicate that the implementation of contextualization was effective in improving students’ vocabulary mastery. It can be seen from the statistical computation result of post-test score of experimental group (M=78.66) that is higher than control group (M=67.33). In reference to the result of this study, it can be concluded that contextualization using REACT is recommended to be applied in teaching vocabulary to elementary students. Moreover, the teachers who are interested in carrying out contextualization need to choose appropriate context based on students’ daily lives or experiences and create a lively classroom atmosphere as well. Keywords:Contextualization, REACT, vocabulary